Jacob Makohin’s Informational “Emissions”: Geopolitical Considerations of a Private Spy about the Post-War Settlement of the World - Monolatii, Ivan (Mediaforum : Analytics, Forecasts, Information Management, 2024)
The article analyzes the attempts of informational manipulation of the public opinion of the Ukrainian diaspora in the USA and Canada after the end of the World War II in 1946–1950 by the American intelligence officer of Ukrainian origin Jacob Makohin (1880–1956). Archival documents from the funds of the National Archives of Canada and the Archives of the Shevchenko Scientific Society in America are published, the contents of which reveal the peculiarities of the information “throwaways” of the American special services regarding the solution of the “Ukrainian problem” after the World War II in the international arena, in which the emphasis is on the problem of “displaced persons”, refugees from Ukrainian ethnic territories, as well as problems of the post-war arrangement of the system of international relations. An important place in these manipulative materials is occupied by the figure of a private spy, who thus becomes an actor of international politics. It is claimed that the published materials can be used for intellectual demystification of the information potential regarding the figure of the American hero and Ukrainian adventurer of the 20th century at the same time, the investigation of the phenomenon of private espionage, the games of intelligence services on the Ukrainian map of the world, the conclusion about the place and role of Ukraine on the chessboard of international relations, the doom of stateless national elites to defeat in the fight against political regimes and their special services. That is why the informational “throws” of J. Makohin can be considered as an explanation of how and why exactly the Ukrainian idea became a hostage of the information wars of major geopolitical players, the political establishment of the West, which disregarded Ukrainian emigration as an institution of world Ukrainians, did everything possible to unite and provoke conflicts between the political environments of Ukrainians on the European and American continents. It is claimed that the media potential of J. Makohin’s information “throw-ins” allows, in particular, to single out the principles of management mechanisms, institutionalization of the power structures of major geopolitical players regarding the Ukrainian issue; the nature and methods of functioning of national and international security systems; the process of expanding the information sphere as a space of influence of information on political and social phenomena in the environment of the Ukrainian diaspora in the USA and Canada.